Dynamic digital object-oriented subscription tree reconstruction method and system - LIU YI; HUANG GANG; JIANG HAI'OU; LUO CHAORAN; JING XIANG (2024)
The invention provides a dynamic digital object-oriented subscription tree reconstruction method and system, and belongs to the technical field of big data. The method comprises the following steps: in response to a subscription adding operation of a subject, obtaining a to-be-added subscription representing a demand of a corresponding subject for digital object metadata; determining a target storage node of the subscriptions to be added in the subscription tree, and determining the number of the subscriptions stored in the target storage node; when the subscription number is greater than a subscription storage threshold value, constructing a subtree of the target storage node according to all the subscriptions stored in the target storage node and subscription attributes corresponding to the subscriptions to be added; and storing all the subscriptions stored in the target storage node and the to-be-added subscriptions in a sub-tree of the target storage node in a scattered manner so as to reconstruct the sub